A pending transition. Women deputies against the female representation in television advertising (1982-1989) - Berdón, Pablo (Historia y Comunicación Social, 2022)
Women increased their presence on TVE with the entry into force of the 1980 Radio and Television Statute, however, the programs and the advertising continued to show a representation of women more in line with the previous regime. This article carries out a critical analysis of the current regulations in charge of the protection of women in TVE advertising. To accomplish this, unpublished documentation from the RTVE board of directors has been reviewed. Also, the main complaints of the deputies in the RTVE control commission have been analyzed. The results show how the women of this committee were at the forefront of the protests against this type of advertising, which is harmful to their image, and called for stricter regulations to promote equality between the sexes.